Characterization of the Immunologic Phenotype of Dendritic Cells Infected With Herpes Simplex Virus 1 - Zhang, Jingjing; Xu, Xingli; Duan, Suqin; Gao, Yang; Ma, Danjing; Yue, Rong; Zeng, Fengyuan; Li, Xueqi; Meng, Ziyan; Li, Xinghang; Niu, Zhenye; Jiang, Guorun; et al. (Frontiers in Immunology, 2022)
Due to viral envelope glycoprotein D binding to cellular membrane HVEM receptor, HSV-1 can infect certain dendritic cells, which becomes an event in the viral strategy to interfere with the host’s immune system. We previously generated the HSV-1 mutant strain M6, which produced an attenuated phenotype in mice and rhesus monkeys. The attenuated M6 strain was used to investigate how HSV-1 infection of dendritic cells interferes with both innate and adaptive immunity. Our study showed that dendritic cells membrane HVEM receptors could mediate infection of the wild-type strain and attenuated M6 strain and that dendritic cells infected by both viruses in local tissues of animals exhibited changes in transcriptional profiles associated with innate immune and inflammatory responses. The infection of pDCs and cDCs by the two strains promoted cell differentiation to the CD103+ phenotype, but varied transcriptional profiles were observed, implying a strategy that the HSV-1 wild-type strain interferes with antiviral immunity, probably due to viral modification of the immunological phenotype of dendritic cells during processing and presentation of antigen to T cells, leading to a series of deviations in immune responses, ultimately generating the deficient immune phenotype observed in infected individuals in the clinical.